Produtividade e qualidade de grãos de híbridos de canola cultivados em diferentes épocas no sudoeste do Paraná - Hrchorovitch, Valtecir Andre (2015)
Canola is the third most important oilseed in global agribusiness. Used in several market segments, its cultivation in Brazil began in the 70s The growth of canola cultivation aimed at producing beans intended for oil extraction can provide high economic efficiency of farms, the choice of the time correct for sowing is essential for this purpose is achieved. Objective of this study was to evaluate the performance of canola hybrids (Hyola 61, Hyola 76, Hyola 411, 433 and Hyola Hyola 571) evaluated in six sowing dates started on 09/03 (1 time) 06/04 (2 times ), 04/05 (3 times), 01/06 (4 times), 29/06 (5 times) and 26/07 (6 times). The experiments were conducted at the Experimental Station of the Federal Technological University of Paraná - UTFPR, Campus Dois Vizinhos. The field experiment was arranged in a randomized block design with split plots in three replications in two years (2013 and 2014 crop). Evaluated the agronomic characteristics as the number of days between emergence and flowering, number of days duration of flowering, number of days between emergency and physiological maturity, average plant height, plant lodging, grain yield, weight a thousand grains, crude protein content in grain and ether extract in the grains. There were significant differences between the effects of the six sowing dates in all variables, including hybrids and years. The study was able to show that it is possible to grow canola in the Southwest of Paraná. Being the first times more responsive sowing and Hyola 411 and Hyola 433 hybrid proved the most suitable among the variables observed.